Tuberculosis in Pregnancy - Lumentut, Anastasia Mariane; Tendean, Hermie; Najoan, Rizki; Islamy, Nurul; Khaerunnisa, Maya; Wirawan, Wahyudi; Maelissa, Merlin (Journal La Medihealtico, 2025)
Tuberculosis (TB) during pregnancy presents significant risks to both the mother and fetus, including complications such as abortion, preterm birth, low birth weight, and postpartum hemorrhage. The immune changes in pregnancy, particularly the shift in TH1/TH2 balance, increase the risk of latent TB reactivation. Diagnosing TB in pregnant women is challenging due to overlapping symptoms with normal pregnancy changes. However, early diagnosis is crucial for effective management, with molecular tests offering assistance, although bacterial culture remains the gold standard. High-risk pregnant women include those with close contact with active TB patients, HIV, immunosuppressive conditions, or severe immunocompromised states such as lymphoma, leukemia, or organ transplant recipients. These women should undergo sputum testing for acid-fast bacilli smear, mycobacterial culture, and nucleic acid amplification testing if TB is suspected. Immunosuppressed patients may require further testing, even if interferon-gamma release assays or tuberculin skin tests are negative. Retesting is recommended eight weeks after exposure to infectious TB. The management of TB in pregnancy involves a multidisciplinary approach, including obstetricians, infectious disease specialists, and neonatologists. First-line anti-TB medications are safe during pregnancy and help prevent maternal and perinatal complications. Treatment for latent TB infection (LTBI) is generally delayed until after delivery. Breastfeeding is safe for mothers on first-line anti-TB medications, as drug levels in breast milk are too low to harm the infant. Early diagnosis, prompt treatment, and proper care are essential to reduce TB-related risks during pregnancy.